Edexcel international GCSE (9-1) Mathematics A1 Student book 1 - Turner, David (London Pearson Education Limited, 2017)
dexcel International GCSE (9-1) Mathematics Student Book 1A is a comprehensive and student-friendly resource designed to support learners preparing for the Edexcel International GCSE Mathematics exam. This book covers the foundational concepts and essential skills required for success in the early stages of the curriculum. It provides clear explanations of key topics, including number theory, algebra, geometry, and data handling, with a strong emphasis on building problem-solving skills. Each chapter features a range of worked examples, practice questions, and real-world applications to reinforce learning and help students develop their mathematical reasoning. With a focus on understanding concepts and improving exam technique, Student Book 1A is an invaluable tool for students seeking to achieve excellence in the Edexcel International GCSE (9-1) Mathematics exam.